2010
DOI: 10.1210/en.2009-0996
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Dopamine D2 Receptor Impairs Insulin Secretion and Causes Glucose Intolerance

Abstract: The relationship between antidopaminergic drugs and glucose has not been extensively studied, even though chronic neuroleptic treatment causes hyperinsulinemia in normal subjects or is associated with diabetes in psychiatric patients. We sought to evaluate dopamine D2 receptor (D2R) participation in pancreatic function. Glucose homeostasis was studied in D2R knockout mice (Drd2(-/-)) mice and in isolated islets from wild-type and Drd2(-/-) mice, using different pharmacological tools. Pancreas immunohistochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 59 publications
(46 reference statements)
6
89
0
1
Order By: Relevance
“…79,84 They might blunt glucosestimulated insulin release by blocking D 2 dopamine receptors or cho linergic stimulated pancreatic insulin secretion by blocking M 3 muscarinic receptors. 85 Studies quantifying the defect in insulin secretion have suggested that certain second generation anti psychotics, for example clozapi ne 75 and quetiapine, 76 might have a greater adverse effect on βcell function than other drugs in this group, at least in the short term. As well as direct effects on βcell func tion, antipsychotics might also affect central control of glucose homeostasis.…”
Section: Mechanismsmentioning
confidence: 99%
“…79,84 They might blunt glucosestimulated insulin release by blocking D 2 dopamine receptors or cho linergic stimulated pancreatic insulin secretion by blocking M 3 muscarinic receptors. 85 Studies quantifying the defect in insulin secretion have suggested that certain second generation anti psychotics, for example clozapi ne 75 and quetiapine, 76 might have a greater adverse effect on βcell function than other drugs in this group, at least in the short term. As well as direct effects on βcell func tion, antipsychotics might also affect central control of glucose homeostasis.…”
Section: Mechanismsmentioning
confidence: 99%
“…Glucose homeostasis was studied in Drd2 –/– mice, and in isolated islets from wild-type and Drd2 –/– mice, using different pharmacological tools [67]. Drd2 –/– mice exhibited an impairment of insulin response to glucose, high fasting glucose levels, and were glucose intolerant.…”
Section: D2rs and Glucose Metabolismmentioning
confidence: 99%
“…Central D2Rs participate not only in control of locomotor activity, executive planning, motor coordination, pain perception, food intake, aggressive and reward-seeking behaviors, but also in the regulation of the GHRH-GH axis (12). Furthermore, lactotrope D2Rs mediate the tonic inhibition that dopamine exerts on prolactin synthesis and release (13), while in the periphery, dopamine regulates pancreatic endocrine function including insulin release from pancreas, and its action on adipocytes (14,15). A link has been established between obesity, growth and dopaminergic systems located both within the central nervous system (CNS) or in other tissues (11,16,17).…”
mentioning
confidence: 99%